Isolation and Identification of Endophyte Fungal from Agarwood Chips - Florence Mitchell, Shiang (Universiti Malaysia Sarawak, (UNIMAS), 2018)
Agarwood is a fragrant wood from non-timber product of the genus Aquilaria. There are very few literatures regarding the isolation and identification of endophyte fungal from agarwood. This study is conducted to isolate and identify the endophyte fungal from agarwood chips. The species of endophyte fungal isolated were identified based on morphological characteristics. Samples of the agarwood were obtained from Ba'kelalan, Sarawak. A total of 20 agarwood chips were placed on PDA, incubated at room temperature for 7 to 14 days to allow the growth of endophyte. The identification of the isolates were done through colony growth morphology and microscopic examination. Out of 8 isolates, seven species of endophyte fungal have been identified. Three isolates AG-1, AG-15(1) and AG-15(2) were identified as Lasiodiplodia sp., two isolates AG- 5 and AG-19 were identified as Aspergillus niger, two isolates AG-11(1) and AG-11(2) were identified as Aspergillus flavus while others AG-2, AG-6, AG-10 (1), and AG-10 (2) were identified as Penicillium sp., Mucor sp., Fusarium solani and Fusarium oxysporum respectively. The endophyte fungal isolated in this study may have the potential to be used as inoculant for agarwood induction in enhancing resin production.